2016
DOI: 10.1017/s0016756816000509
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution and stress pattern of South Wagad Fault at the Kachchh Rift Basin in western India

Abstract: We describe a study of the E–W-trending South Wagad Fault (SWF) complex at the eastern part of the Kachchh Rift Basin (KRB) in Western India. This basin was filled during Late Cretaceous time, and is presently undergoing tectonic inversion. During the late stage of the inversion cycle, all the principal rift faults were reactivated as transpressional strike-slip faults. The SWF complex shows wrench geometry of an anastomosing en échelon fault, where contractional and extensional segments and offsets alternate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…A wide zone of fault rupture pattern is investigated in WH of Kachchh peninsula. The seismic structures, seismicity and fault plane solution investigation show that the GF (F4) is a nearly vertical fault (Figure 7B, C) having dominant strike-slip deformation [15,18,51].…”
Section: Combined Interpretation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide zone of fault rupture pattern is investigated in WH of Kachchh peninsula. The seismic structures, seismicity and fault plane solution investigation show that the GF (F4) is a nearly vertical fault (Figure 7B, C) having dominant strike-slip deformation [15,18,51].…”
Section: Combined Interpretation and Discussionmentioning
confidence: 99%
“…Conventionally, an extensional overstep zone of a strike-slip fault several branches that join together at depth into a single vertical plane [18]. As a consequence, bulk displacement accommodated at depth on the basement fault is distributed towards the surface among several faults whose tectonic activity evolves through time [60].…”
Section: Combined Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information on active faults and its subsurface geometry is essentially needed for effective seismic hazard assessment. Many active fault traces were identified in the region based on field (both geophysical and geological) investigations and satellite photo interpretation, which suggested imprints of Holocene to post Tertiary tectonic activity along the faults (Malik et al 2001;Mathew et al 2006;Patidar et al 2007Patidar et al , 2008Maurya et al 2013;Rajendran et al 2008;Chowksey et al 2011;Bhattacharya et al 2013;Kothyari et al 2016). GPR studies by Patidar et al (2007) indicated reactivation of the Kathrol Hill Fault (KHF) under compressive stress and suggested southward directed tilting of the geomorphic features due to neotectonic movements along the KHF.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of many regional geophysical studies, shallow geophysical surveys done in the region are very limited (Mithila & Bansal, ), except a few site‐specific ground‐penetrating radar studies (Chowksey et al, ; Maurya et al, , ). Using the ground‐penetrating radar and coupled with field investigations, many active fault traces were identified in the region that suggested imprints of Holocene to post‐Tertiary tectonic activity along the faults (Kothyari et al, ; Mathew et al, ; Maurya et al, ; Patidar et al, , ; Prizomwala et al, ; Rajendran et al, ). Chowksey et al () have suggested that the KMF is morphologically expressed as E‐W trending steep scarps, while the actual fault line is located further north and is buried under the Quaternary colluvio‐fluvial sediments.…”
Section: Introductionmentioning
confidence: 99%